Changes in serum TIM-3 and complement C3 expression in workers due to Mn exposure - Qi, Yuanmeng; Si, Huifang; Jin, Xiaofei; Guo, Yonghua; Xia, Jiarui; He, Jing; Deng, Xuedan; Deng, Meng; Yao, Wu; Hao, Changfu (Frontiers in Public Health, 2023)
Mn (Manganese, Mn) is an essential trace element involved in various biological processes such as the regulation of immune, nervous and digestive system functions. However, excessive Mn exposure can lead to immune damage. Occupational workers in cement and ferroalloy manufacturing and other related industries are exposed to low levels of Mn for a long time. Mn exposure is one of the important occupational hazards, but the research on the effect of Mn on the immune system of the occupational population is not complete, and there is no reliable biomarker. Therefore, this study aimed to evaluate the immunotoxicity of Mn from the soluble immune checkpoint TIM-3 (T-cell immunoglobulin and mucin containing protein 3, TIM-3) and complement C3. A total of 144 Mn-exposed workers were recruited from a bus manufacturing company and a railroad company in Henan Province. An inductively coupled plasma mass spectrometer was used to detect the concentration of RBC Mn (Red blood cell Mn, RBC Mn), and ELISA kits were used to detect serum complement C3 and TIM-3. Finally, the subjects were statistically analyzed by dividing them into low and high Mn groups based on the median RBC Mn concentration. We found that Mn exposure resulted in elevated serum TIM-3 expression and decreased complement C3 expression in workers; that serum TIM-3 and complement C3 expression showed a dose–response relationship with RBC Mn; and that the mediating effect of complement C3 between RBC Mn and TIM-3 was found to be significant. The above findings indicate that this study has a preliminary understanding of the effect of Mn exposure on the immune system of the occupational population exposed to Mn, and complement C3 and TIM-3 may be biomarkers of Mn exposure, which may provide clues for the prevention and control of Mn occupational hazards.